Odpowiedzi

2010-03-11T18:15:27+01:00
2 * (-3) + 6 = 0
-5 * (-8) - 16 = 24
2 * (-5) + 3 * (-2) = -16
8 - 6 * (-5) = -38
5 * (-2) - (-2) * 6 = 2
(2*6) * (-8) = -96
-5 * (-6 - 10) = 80
-3 * (-1) - (10) : 4 = 0,5
24 : (-3 * 5) = -0,13333[....]
(8 + 30) : (-7 - 4 ) =3,454545[...]
2010-03-11T18:17:50+01:00
2 * (-3) + 6 = -6+6=0
-5 * (-8) - 16 = 40-16=24
2 * (-5) + 3 * (-2) = -10-6=-16
8 - 6 * (-5) = 8+30=38
5 * (-2) - (-2) * 6 = -10+12=2
(2*6) * (-8) = 12*(-8)=-96
-5 * (-6 - 10) = -5*(-16)=80
-3 * (-1) - (10) : 4 = 3-2,5=0,5
24 : (-3 * 5) = 24:(-15)=-1,6
(8 + 30) : (-7 - 4 ) = 38:(-11)=-3,454545454=-3,5 ( w przybliżeniu)
2010-03-11T18:19:42+01:00
2 * (-3) + 6 =0
-5 * (-8) - 16 =24
2 * (-5) + 3 * (-2) =-16
8 - 6 * (-5) = 38
5 * (-2) - (-2) * 6 = 2
(2*6) * (-8) =-96
-5 * (-6 - 10) =80
-3 * (-1) - (10) : 4 =3-2,5=0,5
24 : (-3 * 5) = -1,6
(8 + 30) : (-7 - 4 ) ≈-3,45